Inclusive Economic Growth in America’s Cities : What’s the Playbook and the Score? - de Souza Briggs, Xavier; Pendall, Rolf; Rubin, Victor (World Bank, Washington, DC, 2015)
This paper defines economic inclusion as the ability of all people, including the disadvantaged, to share in economic gains, that is, the conditions that allow for broadly shared prosperity. Beyond the “right” to access consumption in cities, and beyond relatively standardized safety net policies that support economic security, inclusion demands intentional, flexible, context-appropriate strategies aimed at shifting the dynamics of local land and labor markets, public education, and other institutions. The paper analyzes the varied contexts for designing and supporting such strategies in a rapidly changing society, where urban regions have long been critical to incorporating a broad cross-section of people, including immigrant newcomers. Four dimensions are particularly crucial: an urban area’s level of economic growth, the quality of its jobs, its demographic profile, and its geography of opportunity (degree and form of spatial inequality). Economic inclusion is particularly urgent in America’s strongest local markets, which are pricing out the lowest-wage workers and showing a disturbing tendency to import rather than grow the talent needed for the emerging, innovation-driven economy. But weak-market regions face important challenges—and a range of options for leveraging demographic and other changes—as well. And for now, in all types of cities, innovative and promising strategies remain small in scale, in part because they are competing for support with entrenched, underperforming systems.